2016
DOI: 10.1002/adma.201601248
|View full text |Cite
|
Sign up to set email alerts
|

Broad Detection Range Rhenium Diselenide Photodetector Enhanced by (3‐Aminopropyl)Triethoxysilane and Triphenylphosphine Treatment

Abstract: The effects of triphenylphosphine and (3-aminopropyl)triethoxysilane on a rhenium diselenide (ReSe2 ) photodetector are systematically studied by comparing with conventional MoS2 devices. This study demonstrates a very high performance ReSe2 photodetector with high photoresponsivity (1.18 × 10(6) A W(-1) ), fast photoswitching speed (rising/decaying time: 58/263 ms), and broad photodetection range (possible above 1064 nm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 57 publications
(76 reference statements)
5
59
0
Order By: Relevance
“…Here, the selenium vacancies serving as traps in ReSe 2 seem to possess considerably shorter recombination and generation times for carriers than the sulfur vacancies in ReS 2 . This result agrees well with previous studies on vdW photodetectors, in which considerably shorter photoresponses were confirmed in selenide‐based devices compared to sulfide‐based devices 7, 31. Additionally, we investigated the stability of the photodetectors with respect to the repetitive photoswitching cycle (Figure S4, Supporting Information).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Here, the selenium vacancies serving as traps in ReSe 2 seem to possess considerably shorter recombination and generation times for carriers than the sulfur vacancies in ReS 2 . This result agrees well with previous studies on vdW photodetectors, in which considerably shorter photoresponses were confirmed in selenide‐based devices compared to sulfide‐based devices 7, 31. Additionally, we investigated the stability of the photodetectors with respect to the repetitive photoswitching cycle (Figure S4, Supporting Information).…”
Section: Resultssupporting
confidence: 90%
“…In addition, the other important optoelectronic parameters,38, 39, 40 such as detectivity and external quantum efficiency, were also extracted from the photodetectors fabricated on the ReS 2 , ReSe 2 , and ReS 2 /ReSe 2 heterojunctions; the plotted data is provided in the Supporting Information chapter (Figure S5, Supporting Information). Finally, for performance comparison of the gate‐controllable ReS 2 /ReSe 2 heterojunction photodetector with other devices, we plotted the photoresponsivity values obtained in this study and previous studies for vdW photodetectors4, 5, 6, 7, 8, 9, 10, 11, 13, 23, 41, 42, 43 in Figure 4k. Our gate‐controllable ReS 2 /ReSe 2 heterojunction photodetector (blue dotted line) exhibited relatively high photoresponsivity values over a broad range of wavelengths, compared to other vdW photodetectors.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Here, Φ tip was obtained from the sum of the HOPG work function ( Φ HOPG ) and Δ V CPD between the KPFM tip and the HOPG surface ( Φ tip = Φ HOPG +Δ V CPD_HOPG ), which is presented in more detail in Supplementary Fig. 2 (refs 40, 41). Therefore, the work function values of the BP and ReS 2 films can be estimated to be about 4.5 and 5.1 eV, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most photodetectors were modulated by the applied gate voltage and temperature 85, 176, 177, 178, 188. However, other tuning methods, such as by intercalation or atmosphere, can also enhance the physical properties of the host materials to enhance the optoelectronic performance 14.…”
Section: Applications For 2d Optoelectronic and Electronic Devicesmentioning
confidence: 99%